Advanced zero-optical-distance Mini-LEDs technology with high-luminance composite light-guides for displays - Zhi Ting Ye; Yen Lung Chen; Yu Fu Hsu; Ting Shuo Li; Ku huan Liu; Chun-Nien Liu (International Journal of Optomechatronics)
With the advancement of artificial intelligence technology, there is a growing demand for smart vehicle cockpits. As a result, the performance requirements for automotive displays are increasing. However, commonly used side-light and direct-light backlight modules, which provide planar light sources for displays, struggle to meet the demands for lightweight, thin designs with high uniformity and high luminance simultaneously. Therefore, we propose the use of zero-optical-distance Mini-LEDs in conjunction with a high-luminance composite light-guide for automotive display backlights. This approach involves a direct-side composite light guide that integrates a microstructure of the light incident surface (MLIS). The design includes embedding the light source within perforations and optimizing the curvature to enhance performance. This design expands the distribution, which increases the spacing between light sources and reduces the optical mixing distance (OMD). In this paper, we use an 8.8-inch module for experiments, with a thickness of 3 mm and an input power of 9.72 watts. The module achieves an average luminance of 72,562.3 cd/m2 and a uniformity of 90.79%. This results in a zero-optical-distance, lightweight, thin, and highly uniform high-luminance compound light-guiding planar light-source.